The Use of Vitrification Method For Cryopreservation of Mammalian Oocyte - Pamungkas, Fitra Aji (Indonesian Bulletin of Animal and Veterinary Sciences, 2010)
Technique cryopreservation of oocyte is a way to storage, maintenance, and guarantee the survival of frozen cells. Vitrification is a cryopreservation method which is increasingly popular in reproduction but it is still difficult to be done because of the size, shape, and numbers of oocytes, as well as osmotic shock and fractures. The efforts to improve the method and technique vitrification are by reducing the concentration of cryoprotectants, increasing the cooling rate and warming, recovery of meiotic spindles, and the time of fertilization. Vitrification solution consist of 15% (v/v) ethylene glycol, 15% (v/v) dimethylsulfoxide or 1,2-propanediol, and 0.5 mol/L sucrose was less toxic. Therefore, at 37Â°C, 2 â 3 minutes are usually used for the pretreatment solution and 20 â 30 seconds for exposure to the vitrification solution. In contrast, at room temperature, 5 â 15 minutes are commonly used for pretreatment and 30 â 60 seconds for exposure to the vitrification solution. Warming procedure is performed by direct immersion of the straw into a water bath. Holding the straw in air for 5 seconds before immersion can avoid bursting or performed warming and dilution at 37Â°C. While the time of fertilization performed at 2 â 3 hours after thawing and incubation for oocyte spindle to recover which is essential for the successful of oocyte cryopreservation program. Key words: Cryopreservation, vitrification, oocyte